Analisis Kemampuan Pemecahan Masalah Matematis Siswa dalam Menyelesaikan Masalah Segitiga Berdasarkan Jenis Kelamin - Ita rosita; Andrie Chaerul; Kiki Nia Sania Effendi (Universitas Muria Kudus, 2021)
The purpose of this research is the mathematical problem-solving abilities of male and female students in grade VII Junior High School. The type of research carried out in this research is qualitative with the case study method, using data analysis techniques, namely data analysis model of Miles and Huberman. Activity procedures in data analysis in this study include: data reduction, data presentation, and conclusion drawing. Data collection used test instruments for problem solving abilities on triangular material and unstructured interviews with research subjects. The subjects taken were six students, consisting of three male students and three female students. The data obtained, then analyzed qualitatively. The results of this study indicate that male students are more prominent in the implementation stage only, female students write down the stages of understanding, making, implementing, and checking in order and are more inclined to imitate the previous completion process.